(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This research focuses on the development of an advanced power management and monitoring system for electric cars. The system incorporates several modules, including electric car running power dynamic management, battery maintenance, remote monitoring, electric car induction service, and an intelligent analysis platform. Through the integration of these modules, the system enables effective data acquisition, real-time monitoring, and intelligent analysis of electric car performance. It also facilitates dynamic power management, accurate forecasting of battery life, and enhanced efficiency of electric car operations.